2001
DOI: 10.1590/s0034-89102001000200011
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre cárie, gengivite e fluorose e nível socioeconômico em escolares

Abstract: Resumo ObjetivoDeterminar a relação entre o nível socioeconômico e a prevalência de cárie dentária, gengivite e fluorose em escolares brasileiros. Métodos Foram examinados mil escolares de 12 anos de idade provenientes das redes particular e pública de ensino. Os índices utilizados foram: Índice de Dentes ou Superfícies Cariadas, Perdidas e Obturadas (CPOD ou CPOS), Índice de Sangramento Gengival (ISG) e Índice de Thylstrup e Feyerskov (ITF). O nível socioeconômico foi determinado pela renda per capita e pelo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
1
34

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 10 publications
2
12
1
34
Order By: Relevance
“…Similarly, a study conducted in Porto Alegre, Brazil,28 showed that students from the public school system came from families with lower education levels and that students from the private school network came from families with higher incomes. In our study, approximately 59.2% of the students' mothers were illiterate or had at most completed only the 4th year of school, in contrast with 9.1% of students whose mothers had completed higher education.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, a study conducted in Porto Alegre, Brazil,28 showed that students from the public school system came from families with lower education levels and that students from the private school network came from families with higher incomes. In our study, approximately 59.2% of the students' mothers were illiterate or had at most completed only the 4th year of school, in contrast with 9.1% of students whose mothers had completed higher education.…”
Section: Discussionmentioning
confidence: 94%
“…These may have acted as confounding factors that could have exercised a role that perhaps was more important than the environmental lead contamination in the industrial region. Although the characterization of socioeconomic levels from the education network has been utilized by other researchers, 12 in the present work this appears not to have been a variable that homogenized the groups in relation to similarity of socioeconomic level. Another matter that may have interfered was the greater sample loss in the industrial region.…”
Section: Discussionmentioning
confidence: 93%
“…De acordo com Peres et al 20 , hábitos de consumo de produtos cariogênicos, sobretudo com relação à sua freqüência, parece ser o fator comportamental mais comprovadamente aceito no desenvolvimento do processo carioso. Como o consumo da merenda é praticamente exclusivo em escolas públicas, os atuais resultados podem remeter à similaridade entre os dados achados neste estudo e o observado por Maltz & Silva 21 e em Hoffmann et al 22 que identificaram maior prevalência de cárie em alunos da rede pública, quando comparados com os de escola privada.…”
Section: Discussionunclassified